PENDEKATAN BIONOMI PADA PELUANG PENGEMBANGAN PERIKANAN TANGKAP DI KABUPATEN KEPULAUAN TALAUD - Jeti Pulu; Mulyono S. Baskoro; Daniel R. Monintja; Budhi H. Iskandar; Akhmad Fauzi (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2010)
The research is aimed to reveal opportunity development of the capture fisheries in Talaud Islands Regency by using bionomy approach with Gordon-Schaefer model (Fauzy, 2005) con-cerning the dominant of illegal fishing activities around the area. The research was started by co-llected some secondary data on fish production and number of fishing units. Primary data were collected on catch composition and types of fishing gear. Gordon-Schaefer methods was applied to evaluate the tuna and skipjack resources in the area. The troll and pole and line are indicated as the dominant fishing gears used to catch the skipjack and tuna. In case of open access condition, the production will end up to 25,09 tons, while the resource rent will be end up to zero. For the development, simulations were exercised in 3 scenarios: 1) scenario of enhancing domestic fleet, 2) scenario of illegal fishing, and 3) scenario of net surplus. With those scenarios, if the illegal fishing could be eliminated, the capture fisheries in this regency could render economic value to 10 billion rupiah.